Who Needs Karelian, Kven or Austrian Hungarian – and Why? - Johanna Laakso (Department of European and Comparative Literature and Language Studies, Faculty of Philological and Cultural Studies, University of Vienna) (Peter Lang, 2014)
The abstract is available here: https://uscholar.univie.ac.at/o:313906 The abstract is available here: https://uscholar.univie.ac.at/o:313906 The abstract is available here: https://uscholar.univie.ac.at/o:313906